Soybean GmMYB133 Inhibits Hypocotyl Elongation and Confers Salt Tolerance in Arabidopsis - Shan, Binghui; Wang, Wei; Cao, Jinfeng; Xia, Siqi; Li, Ruihua; Bian, Shaomin; Li, Xuyan (Frontiers in Plant Science, 2021)
REVEILLE (RVE) genes generally act as core circadian oscillators to regulate multiple developmental events and stress responses in plants. It is of importance to document their roles in crops for utilizing them to improve agronomic traits. Soybean is one of the most important crops worldwide. However, the knowledge regarding the functional roles of RVEs is extremely limited in soybean. In the present study, the soybean gene GmMYB133 was shown to be homologous to the RVE8 clade genes of Arabidopsis. GmMYB133 displayed non-rhythmical but salt-inducible expression pattern. Like AtRVE8, overexpression of GmMYB133 in Arabidopsis led to developmental defects such as short hypocotyl and late flowering. Seven light-responsive or auxin-associated genes including AtPIF4 were transcriptionally depressed by GmMYB133, suggesting that GmMYB133 might negatively regulate plant growth. Noticeably, overexpression of GmMYB133 in Arabidopsis promoted seed germination and plant growth under salt stress, and the contents of chlorophylls and MDA were also enhanced and decreased, respectively. Consistently, the expressions of four positive regulators responsive for salt tolerance were remarkably elevated by GmMYB133 overexpression, indicating that GmMYB133 might confer salt stress tolerance. Further observation showed that GmMYB133 overexpression perturbed the clock rhythm of AtPRR5, and yeast one-hybrid assay indicated that GmMYB133 could bind to AtPRR5 promoter. Moreover, the retrieved ChIP-Seq data showed that AtPRR5 could directly target five clients including AtPIF4. Thus, a regulatory module GmMYB133-PRR5-PIF4 was proposed to regulate plant growth and salt stress tolerance. These findings laid a foundation to further address the functional roles of GmMYB133 and its regulatory mechanisms in soybean.